Lesotho : Financial Sector Review - World Bank (Washington, DC, 2013)
This report is a review of the Lesotho's financial system covering: i) the macro-financial environment; ii) safety and soundness of the banking system; iii) non-bank financial institutions; and iv) microfinance and finance for small and medium enterprises. The report was based on data and other information collected during the March 2003 mission. The report is presented in four chapters: chapter one: macro-financial environment and structure of the financial system; chapter two: addresses key issues facing the banking institutions; chapter three: addresses the non-bank financial institutions; and chapter four: addresses the finance for micro, small and medium enterprises. A statistical annex contains relevant data for all the chapters. Overall, the review had three major objectives: a) to assess the safety and soundness of selected sectors in the financial system; b) to evaluate major constraints facing the financial system and its ability to support private sector development; and c) to formulate actions and policies to address these constraints.